Stem cells : a cellular fountain of youth - Mattson, Mark Paul; Van Zant, Gary (Advances in cell aging and gerontology ;, 2002)
This volume provides a timely and thorough review of the current state of understanding of a fascinating type of cell that is capable of forming many or all cells in the body. In humans and other mammals embryonic stem cells, the immediate offspring of the fertilized egg, are capable of forming any type of cell in the body. Moreover stem cells are present in many different tissues in adults that are capable of dividing and differentiating into the specific cell types that comprise the organ in which they reside. A major focus of the book is to provide the reader with up-to-date information on the molecular mechanisms that regulate the proliferation, differentiation and survival of stem cells, and how aging and age-related disease impacts on stem cells. Leading authorities detail the properties and therapeutic potential of embryonic stem cells and stem cells of the nervous and immune systems, muscle and bone. Particularly exciting are emerging technologies for using stem cells to treat human age-related diseases including cardiovascular disease, diabetes, neurodegenerative disorders such as Parkinson's and Alzheimer's diseases. This book will be a valuable reference for developmental biologists and for scientists and clinicians who study and treat a variety of diseases.